Pengenalan Mengenai Gerak Vertikal Kebawah dengan Mengamati Media Mainan Terjun Payung - Nurrahmadani, Annisa; Anjarwati, Nely; Anggraini, Devi; Kurniawati, Wahyu (Indonesian Journal Publisher, 2024)
Vertical downward motion is a phenomenon in physics that occurs when an object falls freely under the influence of gravity without any external force affecting it. In this article, we will look at how vertical downward motion can be observed through the use of skydiving toys. Parachuting toys are used as a safe simulation to observe vertical downward motion. This research uses a descriptive qualitative approach. This approach explains in detail the subject of vertical downward movement through parachuting. The purpose of this article is to introduce an example of vertical downward motion for elementary school children. With this article in order to introduce and invite children to play and know that what is played is an example of vertical downward motion. These toys are often designed with designs and materials that allow the opening or slowing of the fall speed. This ensures that skydiving toys are safer for children to play with. Through observing skydiving toys, we can understand the basic concepts of vertical downward motion and its characteristics such as constant acceleration, terminal velocity, and the design and material factors that affect it. In conclusion, this article shows the importance of vertical downward motion in physics and how skydiving toys can be used to observe this phenomenon.